Dampak Logat Melayu Terhadap Artikulasi Makhorijul Huruf dalam Tilawah Al-Qur'an (Studi Analis pada Santri Tahfiz Darul Falah, Selangor, Malaysia) - Chilmiyah, Rosyidatul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
Reading the Qur'an with the correct makhroj is an obligation, however, non-Arabic speakers, especially Malays, often encounter difficulties in pronouncing the makhroj. This study aims to examine the effect of phonological interference of Malay accent on the articulation of makhorijul letters in reading the Qur'an. This phenomenon is commonly found in tahfiz students in Malaysia who have a Malay mother tongue background, where several Arabic phonemes such as ḥa (ح), ‘ain (ع), qaf (ق), and kha (خ) do not have direct equivalents in the Malay phonological system. This study uses a qualitative descriptive approach with data collection through observation, interviews, and analysis of reading recordings. The subjects of the study consisted of 10 students at the Darul Falah Tahfiz Boarding School, Selangor. The results show that there are systematic errors in the articulation of certain letters which are characterized by phoneme substitution, glottalization, and loss of phonetic properties of letters such as tafkhīm. The discussion is carried out through an applied linguistics approach, language transfer theory, and Arabic phonetics. This study contributes to the development of a more contextual phonetic-contrastive tajwid teaching method for Malay speakers. In addition, this study proposes the integration of classical tajwid science and modern phonetic methods in the curriculum of learning the Qur'an in non-Arab areas.